2003
DOI: 10.1159/000073077
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Involvement in Leukemia – A Study of 288 Cases

Abstract: Two hundred and eighty-eight newly diagnosed cases of leukemia (164 males and 124 females, 167 adults and 121 children, 245 acute and 43 chronic, 151 myeloid and 137 lymphoid), aged between 6 weeks and 78 years, were examined for eye changes in the oncology wards within 2 days of diagnosis before starting chemotherapy. Ocular lesions were present in 102 patients (35.4%) – retinal vascular changes in 91 (31.6%); infiltration of ocular tissues in 5 (1.7%), and neuro-ophthalmic signs in 6 (2.1%) cases. Some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
127
3
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(167 citation statements)
references
References 9 publications
14
127
3
14
Order By: Relevance
“…It is estimated that up to 69% of all patients with leukaemia show fundus changes at some point in the course of their disease. 10 The 55.45% prevalence of leukemic ophthalmopathy documented in the present study is comparable to 69.0% reported by Alemayehu et al, 10 but differed markedly from 35.4% reported by Reddy et al, 11 and 39.0% in a series by Schachat et al 12 The observed disparity could be attributed to the difference in case mix between the present study and those of Reddy et al, and Schachat et al In the present study, the spectrum of leukemic ophthalmopathy showed a preponderance of posterior segment over anterior segment manifestations. These resulted predominantly from secondary hematologic complications caused either by the leukemia itself or its treatment rather than primary leukemic ocular infiltration.…”
Section: Discussionsupporting
confidence: 68%
“…It is estimated that up to 69% of all patients with leukaemia show fundus changes at some point in the course of their disease. 10 The 55.45% prevalence of leukemic ophthalmopathy documented in the present study is comparable to 69.0% reported by Alemayehu et al, 10 but differed markedly from 35.4% reported by Reddy et al, 11 and 39.0% in a series by Schachat et al 12 The observed disparity could be attributed to the difference in case mix between the present study and those of Reddy et al, and Schachat et al In the present study, the spectrum of leukemic ophthalmopathy showed a preponderance of posterior segment over anterior segment manifestations. These resulted predominantly from secondary hematologic complications caused either by the leukemia itself or its treatment rather than primary leukemic ocular infiltration.…”
Section: Discussionsupporting
confidence: 68%
“…These lesions, however, can also occur in persons with conditions other than diabetes, 1 such as hypertension, [2][3][4][5][6] carotid atherosclerotic disease, 7 blood dyscrasias, 8 systemic infections, [9][10][11] and those who have previously undergone radiotherapy. 12 Recent population-based studies in older persons without diabetes have indicated a link between the presence of these retinopathy lesions and an increased risk of subsequent stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In studies where the diagnosis was made during a clinical examination, 17,18 reported prevalence has ranged from 0.4 17 to 0.8%. 18 In studies in which retinal photography was performed and lesions were detected via photographic grading, the prevalence has been found to be much higher: 7.8% in the Beaver Dam Eye Study (BDES), 2 8.3% in the Cardiovascular Health Study (CHS), 19 and 9.8% in the Blue Mountains Eye Study (BMES). 5 The BDES reported a 5-year retinopathy incidence of 6.0% in persons aged 43-86 years and without diabetes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The Red blood corpuscles were microcytic and hypochromic. Platelets were reduced to 89,000 cells/mm 3 . Hb was 9.8 gm/dl.…”
Section: Case Presentationmentioning
confidence: 99%
“…Patient came to ophthalmology OPD with complaints of diminution of vision in both eyes since 2 days. On taking history it was a sudden painless in nature with Best corrected visual acuity of 20/60 both eyes for distant and near N [3] both eyes. Anterior segment on torch light and slit lamp examination case out to be within normal limit in both eyes.…”
Section: Case Presentationmentioning
confidence: 99%